Assessing the prevalence of compromised bone health among overweight and obese African-American breast cancer survivors: a case control study - Sheean, Patricia (J Cancer Surviv, 2015)
PURPOSE: Osteoporosis increases the risk of fracture and is often considered a late effect of breast cancer treatment. We examined the prevalence of compromised bone health in a sample of exclusively African-American (AA) breast cancer survivors since bone mineral density (BMD) varies by race/ethnicity in healthy populations. METHODS: Using a case-control design, AA women in a weight loss intervention previously diagnosed and treated for Stage I-IIIa breast cancer were matched 1:1 on age, race, sex and BMI with non-cancer population controls (n=101 pairs) from NHANES. Questionnaires and dual energy x-ray absorptiometry (DXA) scanning were completed and participants were categorized as having normal bone density, low bone mass or osteoporosis using the WHO definition for femoral neck T-scores. RESULTS: The majority of these overweight/obese survivors were 6.6 (± 4.7) years post-diagnosis, had Stage II (n=46) or Stage III (n=16) disease, and treated with chemotherapy (76%), radiation (72%) and/or adjuvant hormone therapies (45%). Mean femoral neck BMD was significantly lower in cases vs. matched non-cancer population controls (0.85 ± 0.15 vs. 0.91 ± 0.14 g/cm(2), respectively; p=0.007). However, the prevalence of low bone mass and osteoporosis was low and did not significantly differ between groups (n=101 pairs; p=0.26), even when restricted to those on adjuvant hormone therapies (n=45 pairs; p=0.75). Using conditional logistic regression, controlling for dietary factors and education, the odds of developing compromised bone health in AA breast cancer survivors was insignificant (OR 1.5, 95% CI 0.52, 5.56). CONCLUSIONS: These null case-control findings challenge the clinical assumption that osteoporosis is highly prevalent among all breast cancer survivors, providing foundational evidence to support differences by race/ethnicity and body weight. IMPLICATIONS FOR CANCER SURVIVORS: Routine bone density testing and regular patient-provider dialogue is critical in overweight/obese AA breast cancer survivors to ensure that healthy lifestyle factors (e.g., ideal weight, regular weight-bearing exercises, dietary adequacy of calcium and vitamin D) support optimal skeletal health.